Relational Agency of University Teachers of Chinese as a Second Language: A Personal Network Perspective - Yang, Weijia; Li, Citing; Gao, Xuesong (Frontiers in Psychology, 2022)
Relational agency is pivotal for understanding how language teachers seek and utilize relational resources in different contexts and grow to be agents of change amid various educational challenges.This study explored how three university teachers of Chinese as a second language (CSL) enacted their relational agency to enhance their research capacity and sustain their professional development. Data on their personal network development was collected through concentric circle interviews, life-history interviews and written reflections over three months. Thematic analysis was adopted for iterative coding and interpretationof the data. The findings revealed that teachers’ personal networks provided them with value guidance, emotional support and academic support, which exerted differential levels of impact on them to make agentic choices and actions. The study suggests that personal network analysis may serve as a suitable theoretical lens to achieve a multilayered understanding of relational agency. The study also calls for more efforts to create learning opportunities and spaces in the relational context for teachers to build their career as agentic academics in language teacher education and development programs.